New low order Runge–Kutta schemes for asymptotically exact global error estimation of embedded methods without order reduction - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Turn all the lights off: Bright- and dark-field second-harmonic microscopy to select contrast mechanisms for ferroelectric domain walls - Hegarty, Peter A.; Beccard, Henrik; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Recent analyses by polarization resolved second-harmonic (SH) microscopy have demonstrated that ferroelectric (FE) domain walls (DWs) can possess non-Ising wall characteristics and topological nature. These analyses rely on locally analyzing the properties, directionality, and magnitude of the second-order nonlinear tensor. However, when inspecting FE DWs with SH microscopy, a manifold of different effects may contribute to the observed signal difference between domains and DWs, i.e., far-field interference, Čerenkov-type phase-matching (CSHG), and changes in the aforementioned local nonlinear optical properties. They all might be present at the same time and, therefore, require careful interpretation and separation. In this work, we demonstrate how the particularly strong Čerenkov-type contrast can selectively be blocked using dark- and bright-field SH microscopy. Based on this approach, we show that other contrast mechanisms emerge that were previously overlayed by CSHG but can now be readily selected through the appropriate experimental geometry. Using the methods presented, we show that the strength of the CSHG contrast compared to the other mechanisms is approximately 22 times higher. This work lays the foundation for the in-depth analysis of FE DW topologies by SH microscopy.
Keywords: General Physics and Astronomy

Nonlinear optical interactions in focused beams and nanosized structures - Amber, Zeeshan H.; Spychala, Kai J.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Thin-film materials from μm thickness down to single-atomic-layered 2D materials play a central role in many novel electronic and optical applications. Coherent, nonlinear optical (NLO) μ-spectroscopy offers insight into the local thickness, stacking order, symmetry, or electronic and vibrational properties. Thin films and 2D materials are usually supported on multi-layered substrates leading to (multi-)reflections, interference, or phase jumps at interfaces during μ-spectroscopy, which all can make the interpretation of experiments particularly challenging. The disentanglement of the influence parameters can be achieved via rigorous theoretical analysis. In this work, we compare two self-developed modeling approaches, a semi-analytical and a fully vectorial model, to experiments carried out in thin-film geometry for two archetypal NLO processes, second-harmonic and third-harmonic generation. In particular, we demonstrate that thin-film interference and phase matching do heavily influence the signal strength. Furthermore, we work out key differences between three and four photon processes, such as the role of the Gouy-phase shift and the focal position. Last, we can show that a relatively simple semi-analytical model, despite its limitations, is able to accurately describe experiments at a significantly lower computational cost as compared to a full vectorial modeling. This study lays the groundwork for performing quantitative NLO μ-spectroscopy on thin films and 2D materials, as it identifies and quantifies the impact of the corresponding sample and setup parameters on the NLO signal, in order to distinguish them from genuine material properties.<
Keywords: General Physics and Astronomy

Tuning the Čerenkov second harmonic contrast from ferroelectric domain walls via anomalous dispersion - Hegarty, Peter A.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Second harmonic (SH) microscopy represents a powerful tool for the investigation of crystalline systems, such as ferroelectrics and their domain walls (DWs). Under the condition of normal dispersion, i.e., the refractive index at the SH wavelength is larger as compared to the refractive index at the fundamental wavelength, n(2ω)>n(ω), bulk crystals will generate no SH signal. Should the bulk, however, contain DWs, an appreciable SH signal will still be detectable at the location of DWs stemming from the Čerenkov mechanism. In this work, we demonstrate both how SH signals are generated in bulk media and how the Čerenkov mechanism can be inhibited by using anomalous dispersion, i.e., n(ω)<n(2ω). This allows us to quantitatively estimate the relative strength of the Čerenkov compared to other SH contrast mechanisms in DWs, such as the interference contrast. The results are in agreement with previous experiments based on the geometric separation of the signals. Due to the observed, strong Čerenkov contrast, such signal contributions may not be neglected in polarimetry studies of ferroelectric DWs in the future.
Keywords: General Physics and Astronomy

Threshold photoelectron spectroscopy of trimethylborane and its pyrolysis products - Schleier, Domenik; Gerlach, Marius; Schaffner, Dorothee; Mukhopadhyay, Deb Pratim; Hemberger, Patrick; Fischer, Ingo (Physical Chemistry Chemical Physics)
A new decomposition mechanism for trimethylborane at high temperatures has been discovered.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Investigation of the combustion chemistry in laminar, low-pressure oxymethylene ether flames (OME0–4) - Gaiser, Nina; Zhang, Hao; Bierkandt, Thomas; Schmitt, Steffen; Zinsmeister, Julia; Kathrotia, Trupti; Hemberger, Patrick; Shaqiri, Shkelqim; Kasper, Tina; Aigner, Manfred; Oßwald, Patrick; Köhler, Markus (Combustion and Flame)
Quantitative speciation data for alternative fuels is highly desired to assess their emission potential and to develop and validate chemical kinetic models. In terms of substitute choices for fossil diesel are oxymethylene ethers (OMEs) strongly discussed. Due to the absence of carbon-carbon bonds, soot emis-sions from combustion of OMEs are low, but significant emissions of unregulated pollutants such as alde-hydes emerge. The combustion behavior of OME fuels with different chain lengths, OME0-4, was investigated in lam-inar premixed low-pressure flames using complementary molecular-beam mass spectrometry (MBMS) techniques. MBMS sampling provides an in-situ access directly into the reaction zone of the flame. Al-most all chemical species involved in the oxidation process can be detected and quantified simultane-ously. Neat OME0-3 flames were analyzed by electron ionization (EI) MBMS with high mass resolution ( R approximate to 3900) providing exact elementary composition. To obtain isomer-specific information, an OME1- doped hydrogen flame and a stochiometric OME4 flame were studied by double-imaging photoelectron photoion coincidence (i2PEPICO) spectroscopy. Both, EI-MBMS detection and i2PEPICO spectroscopy, en-ables a complete overview of all intermediates. The results show a dominance of oxygenated intermediates for all measured conditions. Mole fraction profiles for the most important species are presented (i.e. formaldehyde, methanol, methyl formate and formic acid) and compared to modeling results. Hydrocarbons with more than four carbon atoms were not detected under the investigated conditions. Isomers such as ethanol/dimethyl ether (m/z = 46) and ethenol/acetaldehyde (m/z = 44) could be separated using threshold photoelectron spectra for clear iden-tification and photoionization efficiency curves for quantification. This investigation permits the discus-sion and analysis of systematic trends, including intermediate species, for the combustion of the studied series of oxymethylene ether fuels. (c) 2022 The Combustion Institute. Published by Elsevier Inc. All rights reserved.
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

On the diversity of fossil and alternative gasoline combustion chemistry: A comparative flow reactor study - Zinsmeister, Julia; Gaiser, Nina; Melder, Jens; Bierkandt, Thomas; Hemberger, Patrick; Kasper, Tina; Aigner, Manfred; Köhler, Markus; Oßwald, Patrick (Combustion and Flame)
Recent progress in molecular combustion chemistry allows for detailed investigation of the intermediate species pool even for complex chemical fuel compositions, as occur for technical fuels. This study pro-vides detailed investigation of a comprehensive set of complex alternative gasoline fuels obtained from laminar flow reactors equipped with molecular-beam sampling techniques for observation of the com-bustion intermediate species pool in homogeneous gas phase reactions. The combination of ionization techniques including double-imaging photoelectron photoion coincidence (i2PEPICO) spectroscopy enables deeper mechanistic insights into the underlying reaction network relevant to technical fuels. The se-lected fuels focus on contemporary automotive engine application as drop-in fuels compliant to European EN 228 specification for gasoline. Therefore, potential alternative gasoline blends containing oxygenated hydrocarbons as octane improvers obtainable from bio-technological production routes, e.g., ethanol, iso- butanol, methyl tert -butyl ether (MTBE), and ethyl tert -butyl ether (ETBE), as well as a Fischer-Tropsch surrogate were investigated. The fuel set is completed by two synthetic naphtha fractions obtained from Fischer-Tropsch and methanol-to-gasoline processes alongside with a fossil reference gasoline. In total, speciation data for 11 technical fuels from two atmospheric flow reactor setups are presented. Detailed main and intermediate species profiles are provided for slightly rich ( 4) = 1.2) and lean ( 4) = 0.8) con-ditions for intermediate to high temperatures. Complementary, the isomer distribution on different mass channels, like m/z = 78 u fulvene/benzene, of four gasolines was investigated. Experimental findings are analyzed in terms of the detailed fuel composition and literature findings for molecular combustion chemistry. Influences of oxygenated fuel components as well as composition of the hydrocarbon frac-tions are examined with a particular focus on the soot precursor chemistry. This dataset is available for validation of chemical kinetic mechanisms for realistic gasolines containing oxygenated hydrocarbons.(c) 2021 The Combustion Institute. Published by Elsevier Inc. All rights reserved.
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Measurement and modelling solubility of amino acids and peptides in aqueous 2-propanol solutions - Do, Hoang Tam; Franke, Patrick; Volpert, Sophia; Klinksiek, Marcel; Thome, Max; Held, Christoph (Physical Chemistry Chemical Physics)
In this work the solubility of 15 amino acids and 18 peptides in aqueous 2-propanol solutions was successfully modelled using PC-SAFT that used recently determined experimental melting properties as input data.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Artificial neural networks for the kinetic energy functional of non-interacting fermions - Ghasemi, Alireza; Kühne, Thomas (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

An automated approach for developing neural network interatomic potentials with FLAME - Mirhosseini, Hossein; Tahmasbi, Hossein; Kuchana, Sai Ram; Ghasemi, Alireza; Kühne, Thomas (Computational Materials Science)
Keywords: Computational Mathematics; General Physics and Astronomy; Mechanics of Materials; General Materials Science; General Chemistry; General Computer Science

The potential and global outlook of integrated photonics for quantum technologies - Pelucchi, Emanuele; Fagas, Giorgos; Aharonovich, Igor; Englund, Dirk; Figueroa, Eden; Gong, Qihuang; Hannes, Hübel; Liu, Jin; Lu, Chao-Yang; Matsuda, Nobuyuki; Pan, Jian-Wei; Schreck, Florian; et al. (Nature Reviews Physics)
Keywords: General Physics and Astronomy

Thermostable water reservoirs in the interlayer space of a sodium hectorite clay through the intercalation of γ-aminopropyl(dimethyl)ethoxysilane in toluene - Keil, Waldemar; Zhao, Kai; Oswald, Arthur; Bremser, Wolfgang; Schmidt, Claudia; Hintze-Bruening, Horst (Physical Chemistry Chemical Physics)
Thermostable compartmentalized sodium-water sites through intercalated γ-aminopropyl-dimethyl-ethoxy silane in synthetic hectorite.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Low-field onset of Wannier-Stark localization in a polycrystalline hybrid organic inorganic perovskite - Berghoff, Daniel; Bühler, Johannes; Bonn, Mischa; Leitenstorfer, Alfred; Meier, Torsten; Kim, Heejae (Nature Communications)
Abstract Methylammonium lead iodide perovskite (MAPbI 3 ) is renowned for an impressive power conversion efficiency rise and cost-effective fabrication for photovoltaics. In this work, we demonstrate that polycrystalline MAPbI 3 s undergo drastic changes in optical properties at moderate field strengths with an ultrafast response time, via transient Wannier Stark localization. The distinct band structure of this material - the large lattice periodicity, the narrow electronic energy bandwidths, and the coincidence of these two along the same high-symmetry direction – enables relatively weak fields to bring this material into the Wannier Stark regime. Its polycrystalline nature is not detrimental to the optical switching performance of the material, since the least dispersive direction of the band structure dominates the contribution to the optical response, which favors low-cost fabrication. Together with the outstanding photophysical properties of MAPbI 3 , this finding highlights the great potential of this material in ultrafast light modulation and novel photonic applications.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Relaxed parameter conditions for chemotactic collapse in logistic-type parabolic–elliptic Keller–Segel systems - Black, Tobias; Fuest, Mario; Lankeit, Johannes (Zeitschrift für angewandte Mathematik und Physik)
Keywords: Applied Mathematics; General Physics and Astronomy; General Mathematics

Prescribed signal concentration on the boundary: Weak solvability in a chemotaxis-Stokes system with proliferation - Black, Tobias; Wu, Chunyan (Zeitschrift für angewandte Mathematik und Physik)
Keywords: Applied Mathematics; General Physics and Astronomy; General Mathematics

Robust ferroelectric polarization retention in harsh environments through engineered domain wall pinning - Zhang, Dawei; Sando, Daniel; Pan, Ying; Sharma, Pankaj; Seidel, Jan (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Diffusion of the carbon dioxide–ethanol mixture in the extended critical region - Chatwell, René Spencer; Guevara-Carrion, Gabriela; Gaponenko, Yuri; Shevtsova, Valentina; Vrabec, Jadran (Physical Chemistry Chemical Physics)
The effect of traces of ethanol in supercritical carbon dioxide on the mixture's thermodynamic properties is studied by molecular simulations and Taylor dispersion measurements.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Quantifying the coherent interaction length of second-harmonic microscopy in lithium niobate confined nanostructures - Amber, Zeeshan H.; Kirbus, Benjamin; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Thin-film lithium niobate (TFLN) in the form of x- or z-cut lithium-niobate-on-insulator has attracted considerable interest as a very promising and novel platform for developing integrated optoelectronic (nano)devices and exploring fundamental research. Here, we investigate the coherent interaction length lc of optical second-harmonic generation (SHG) microscopy in such samples, that are purposely prepared into a wedge shape, in order to elegantly tune the geometrical confinement from bulk thicknesses down to approximately 50 nm. SHG microscopy is a very powerful and non-invasive tool for the investigation of structural properties in the biological and solid-state sciences, especially for visualizing and analyzing ferroelectric domains and domain walls. However, unlike in bulk lithium niobate (LN), SHG microscopy in TFLN is impacted by interfacial reflections and resonant enhancement, both of which rely on film thickness and substrate material. In this paper, we show that the dominant SHG contribution measured on TFLN in backreflection is the co-propagating phase-matched SHG signal and not the counter-propagating SHG portion as is the case for bulk LN samples. Moreover, lc depends on the incident pump laser wavelength (sample dispersion) but also on the numerical aperture of the focussing objective in use. These experimental findings on x- and z-cut TFLN are excellently backed up by our advanced numerical simulations.
Keywords: General Physics and Astronomy

Dimethyl ether (DME) and dimethoxymethane (DMM) as reaction enhancers for methane: Combining flame experiments with model-assisted exploration of a polygeneration process - Zhang, Hao; Kaczmarek, Dennis; Rudolph, Charlotte; Schmitt, Steffen; Gaiser, Nina; Oßwald, Patrick; Bierkandt, Thomas; Kasper, Tina; Atakan, Burak; Kohse-Höinghaus, Katharina (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

In silico investigation of Cu(In,Ga)Se2-based solar cells - Mirhosseini, Hossein; Kormath Madam Raghupathy, Ramya; Sahoo, Sudhir K.; Wiebeler, Hendrik; Chugh, Manjusha; Kühne, Thomas D. (Physical Chemistry Chemical Physics)
State-of-the-art methods in materials science such as artificial intelligence and data-driven techniques advance the investigation of photovoltaic materials.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Tumbling with a limp: local asymmetry in water's hydrogen bond network and its consequences - Elgabarty, Hossam; Kühne, Thomas (Physical Chemistry Chemical Physics)
Ab initio molecular dynamics simulations of ambient liquid water and energy decomposition analysis have recently shown that water molecules exhibit significant asymmetry between the strengths of the two donor and/or the two acceptor interactions.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Effects of KF and RbF treatments on Cu(In,Ga)Se2-based solar cells: A combined photoelectron spectroscopy and DFT study - Majumdar, I.; Sahoo, S.K.; Parvan, V.; Mirhosseini, Hossein; Chacko, B.; Wang, Y.; Greiner, D.; Kühne, Thomas; Schlatmann, R.; Lauermann, I. (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

C 2 N: A Class of Covalent Frameworks with Unique Properties - Tian, Zhihong; Lopez Salas, Nieves; Liu, Chuntai; Liu, Tianxi; Antonietti, Markus (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Key activity descriptors of nickel-iron oxygen evolution electrocatalysts in the presence of alkali metal cations - Görlin, Mikaela; Halldin Stenlid, Joakim; Koroidov, Sergey; Wang, Hsin-Yi; Börner, Mia; Shipilin, Mikhail; Kalinko, Aleksandr; Murzin, Vadim; Safonova, Olga V.; Nachtegaal, Maarten; Uheida, Abdusalam; Dutta, Joydeep; et al. (Nature Communications)
Abstract Efficient oxygen evolution reaction (OER) electrocatalysts are pivotal for sustainable fuel production, where the Ni-Fe oxyhydroxide (OOH) is among the most active catalysts for alkaline OER. Electrolyte alkali metal cations have been shown to modify the activity and reaction intermediates, however, the exact mechanism is at question due to unexplained deviations from the cation size trend. Our X-ray absorption spectroelectrochemical results show that bigger cations shift the Ni 2+/(3+δ)+ redox peak and OER activity to lower potentials (however, with typical discrepancies), following the order CsOH > NaOH ≈ KOH > RbOH > LiOH. Here, we find that the OER activity follows the variations in electrolyte pH rather than a specific cation, which accounts for differences both in basicity of the alkali hydroxides and other contributing anomalies. Our density functional theory-derived reactivity descriptors confirm that cations impose negligible effect on the Lewis acidity of Ni, Fe, and O lattice sites, thus strengthening the conclusions of an indirect pH effect.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Exploring the light-induced dynamics in solvated metallogrid complexes with femtosecond pulses across the electromagnetic spectrum - Naumova, Maria A.; Kalinko, Aleksandr; Wong, Joanne W. L.; Alvarez Gutierrez, Sol; Meng, Jie; Liang, Mingli; Abdellah, Mohamed; Geng, Huifang; Lin, Weihua; Kubicek, Katharina; Biednov, Mykola; Lima, Frederico; et al. (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Poling thin-film x-cut lithium niobate for quasi-phase matching with sub-micrometer periodicity - Zhao, Jie; Rüsing, Michael; Roeper, Matthias; Eng, Lukas M.; Mookherjea, Shayan (Journal of Applied Physics)
Quasi-phase-matched grating structures in lithium niobate waveguides with sub-micrometer periodicities will benefit the development of short-wavelength nonlinear optical devices. Here, we report on the reproducible formation of periodically poled domains in x-cut single-crystalline thin-film lithium niobate with periodicities as short as 600 nm. Shaped single-voltage poling pulses were applied to electrode structures that were fabricated by a combination of electron-beam and direct-writing laser lithography. Evidence of successful poling with good quality was obtained through second-harmonic microscopy and piezoresponse force microscopy imaging. For the sub-micrometer period structures, we observed patterns with a double periodicity formed by domain interactions and features with sizes <200 nm.
Keywords: General Physics and Astronomy

High Quality Entangled Photon Pair Generation in Periodically Poled Thin-Film Lithium Niobate Waveguides - Zhao, Jie; Ma, Chaoxuan; Rüsing, Michael; Mookherjea, Shayan (Physical Review Letters)
Keywords: General Physics and Astronomy

Calculating the distributions of number, mass and luminosity of the stars with the help of MS Excel - Hohmann, Sascha (European Journal of Physics)
Abstract Astrophysical topics can be treated with the methods of different areas of physics, mathematics and other natural sciences. The integration of these topics into such areas could improve students’ motivation and strengthen the connections between different fields of the mentioned sciences. In this article, an example of the connection between the physics of the stars and that of their statistical distributions is given. The usage of Microsoft Excel simplifies the mathematical requirements and gives the possibility of seeing the changes of distribution with the growing age of the regarded population of stars. The changes are a direct consequence to the limited lifetime of the stars and the limited age of the considered population of stars.
Keywords: General Physics and Astronomy

Azlactone-functionalized smart block copolymers for organocatalyst immobilization - Yu, Xiaoqian; Herberg, Artjom; Kuckling, Dirk (European Polymer Journal)
Keywords: Organic Chemistry; Polymers and Plastics; General Physics and Astronomy; Materials Chemistry

Experimental and numerical study of polyoxymethylene (Aldrich) combustion in counterflow - Glaznev, Roman K.; Karpov, Alexander I.; Korobeinichev, Oleg P.; Bolkisev, Andrei A.; Shaklein, Artem A.; Shmakov, Andrey G.; Paletsky, Alexander A.; Gonchikzhapov, Munko B.; Kumar, Amit (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Chemistry of iron nitrate-based precursor solutions for spray-flame synthesis - Stodt, Malte F. B.; Gonchikzhapov, Munko; Kasper, Tina; Fritsching, Udo; Kiefer, Johannes (Physical Chemistry Chemical Physics)
Understanding the chemistry of precursor solutions for spray-flame synthesis is a key step to developing inexpensive and large scale applications for tailored nanoparticles.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Estimating the Indistinguishability of Heralded Single Photons Using Second-Order Correlation - Faruque, Imad I.; Sinclair, Gary F.; Bonneau, Damien; Ono, Takafumi; Silberhorn, Christine; Thompson, Mark G.; Rarity, John G. (Physical Review Applied)
Keywords: General Physics and Astronomy

Second harmonic microscopy of poled x-cut thin film lithium niobate: Understanding the contrast mechanism - Rüsing, Michael; Zhao, J.; Mookherjea, S. (Journal of Applied Physics)
Thin film lithium niobate has been of great interest recently, and an understanding of periodically poled thin films is crucial for both fundamental physics and device developments. Second-harmonic (SH) microscopy allows for the noninvasive visualization and analysis of ferroelectric domain structures and walls. While the technique is well understood in bulk lithium niobate, SH microscopy in thin films is largely influenced by interfacial reflections and resonant enhancements, which depend on film thicknesses and substrate materials. We present a comprehensive analysis of SH microscopy in x-cut lithium niobate thin films, based on a full three-dimensional focus calculation and accounting for interface reflections. We show that the dominant signal in backreflection originates from a copropagating phase-matched process observed through reflections, rather than direct detection of the counterpropagating signal as in bulk samples. We simulate the SH signatures of domain structures by a simple model of the domain wall as an extensionless transition from a −χ(2) to a +χ(2) region. This allows us to explain the main observation of domain structures in the thin-film geometry, and, in particular, we show that the SH signal from thin poled films allows to unambiguously distinguish areas, which are completely or only partly inverted in depth.
Keywords: General Physics and Astronomy

Ergodic Rate for Fading Interference Channels with Proper and Improper Gaussian Signaling - Soleymani, Mohammad; Santamaria, Ignacio; Lameiro, Christian; Schreier, Peter J. (Entropy)
This paper studies the performance of improper Gaussian signaling (IGS) over a 2-user Rayleigh single-input single-output (SISO) interference channel, treating interference as noise. We assume that the receivers have perfect channel state information (CSI), while the transmitters have access to only statistical CSI. Under these assumptions, we consider a signaling scheme, which we refer to as proper/improper Gaussian signaling or PGS/IGS, where at most one user may employ IGS. For the Rayleigh fading channel model, we characterize the statistical distribution of the signal-to-interference-plus-noise ratio at each receiver and derive closed-form expressions for the ergodic rates. By adapting the powers, we characterize the Pareto boundary of the ergodic rate region for the 2-user fading IC. The ergodic transmission rates can be attained using fixed-rate codebooks and no optimization is involved. Our results show that, in the moderate and strong interference regimes, the proposed PGS/IGS scheme improves the performance with respect to the PGS scheme. Additionally, we numerically compute the ergodic rate region of the full IGS scheme when both users can employ IGS and their transmission parameters are optimized by an exhaustive search. Our results suggest that most of the Pareto optimal points for the 2-user fading IC channel are attained when either both users transmit PGS or when one transmits PGS and the other transmits maximally improper Gaussian signals and time sharing is allowed.
Keywords: General Physics and Astronomy

Quantum-Limited Time-Frequency Estimation through Mode-Selective Photon Measurement - Donohue, J. M.; Ansari, V.; Řeháček, J.; Hradil, Z.; Stoklasa, B.; Paúr, M.; Sánchez-Soto, L. L.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Liquid-liquid phase separation in dilute solutions of poly(styrene sulfonate) with multivalent cations: Phase diagrams, chain morphology, and impact of temperature - Hansch, Markus; Hämisch, Benjamin; Schweins, Ralf; Prévost, Sylvain; Huber, Klaus (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Polyacrylates in the presence of an extraordinary monovalent cation—Solution behavior and metal nanoparticle formation - Urbanski, Anna; Hansch, Markus; Lopez, Carlos G.; Schweins, Ralf; Hertle, Yvonne; Hellweg, Thomas; Polzer, Frank; Huber, Klaus (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Reaction enthalpy from the binding of multivalent cations to anionic polyelectrolytes in dilute solutions - Hansch, Markus; Kaub, Hans Peter; Deck, Sascha; Carl, Nico; Huber, Klaus (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Structural heterogeneity in a parent ground-state structure of AnPixJg2 revealed by theory and spectroscopy - Scarbath-Evers, Laura Katharina; Jähnigen, Sascha; Elgabarty, Hossam; Song, Chen; Narikawa, Rei; Matysik, Jörg; Sebastiani, Daniel (Physical Chemistry Chemical Physics)
Extensive molecular dynamics simulations reveal two distinct isoforms of the cyanobacteriochrome AnPixJg2 (in its Pr state) with different chromophore conformations, yielding implications for spectroscopic properties.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

An experimental study of horizontal flame spread over PMMA surface in still air - Korobeinichev, Oleg; Gonchikzhapov, Munko; Tereshchenko, Alexander; Gerasimov, Ilya; Shmakov, Andrey; Paletsky, Alexander; Karpov, Alexander (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Reline aqueous solutions behaving as liquid mixtures of H-bonded co-solvents: microphase segregation and formation of co-continuous structures as indicated by Brillouin and 1H NMR spectroscopies - Posada, E.; Lopez Salas, Nieves; Jiménez Riobóo, R. J.; Ferrer, M. L.; Gutiérrez, M. C.; del Monte, F. (Physical Chemistry Chemical Physics)
Deep eutectic solvents (DESs) offer a suitable alternative to conventional solvents in terms of both performance and cost-effectiveness.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

High-Efficiency Plug-and-Play Source of Heralded Single Photons - Montaut, Nicola; Sansoni, Linda; Meyer-Scott, Evan; Ricken, Raimund; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (Physical Review Applied)
Keywords: General Physics and Astronomy

Extracting the physical sector of quantum states - Mogilevtsev, D; Teo, Y S; Řeháček, J; Hradil, Z; Tiedau, J; Kruse, R; Harder, G; Silberhorn, Christine; Sanchez-Soto, L L (New Journal of Physics)
Keywords: General Physics and Astronomy

Talbot Effect for Exciton Polaritons - Gao, T.; Estrecho, E.; Li, G.; Egorov, O. A.; Ma, Xuekai; Winkler, K.; Kamp, M.; Schneider, C.; Höfling, S.; Truscott, A. G.; Ostrovskaya, E. A. (Physical Review Letters)
Keywords: General Physics and Astronomy

Blow-up of weak solutions to a chemotaxis system under influence of an external chemoattractant - Black, Tobias (Nonlinearity)
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Counterflow flames of ultrahigh-molecular-weight polyethylene with and without triphenylphosphate - Korobeinichev, O.P.; Gonchikzhapov, M.B.; Paletsky, A.A.; Tereshchenko, A.G.; Shundrina, I.K.; Kuibida, L.V.; Shmakov, A.G.; Hu, Y. (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Engineering the Frequency Spectrum of Bright Squeezed Vacuum via Group Velocity Dispersion in an SU(1,1) Interferometer - Lemieux, Samuel; Manceau, Mathieu; Sharapova, Polina; Tikhonova, Olga V.; Boyd, Robert W.; Leuchs, Gerd; Chekhova, Maria V. (Physical Review Letters)
Keywords: General Physics and Astronomy

Quantum technology: from research to application - Schleich, Wolfgang P.; Ranade, Kedar S.; Anton, Christian; Arndt, Markus; Aspelmeyer, Markus; Bayer, Manfred; Berg, Gunnar; Calarco, Tommaso; Fuchs, Harald; Giacobino, Elisabeth; Grassl, Markus; Hänggi, Peter; et al. (Applied Physics B)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

Local Sampling of the Wigner Function at Telecom Wavelength with Loss-Tolerant Detection of Photon Statistics - Harder, G.; Silberhorn, Christine; Rehacek, J.; Hradil, Z.; Motka, L.; Stoklasa, B.; Sánchez-Soto, L. L. (Physical Review Letters)
Keywords: General Physics and Astronomy

“On-the-fly” coupled cluster path-integral molecular dynamics: impact of nuclear quantum effects on the protonated water dimer - Spura, Thomas; Elgabarty, Hossam; Kühne, Thomas (Physical Chemistry Chemical Physics)
“On-the-fly” coupled cluster-based path-integral molecular dynamics simulations predict that the effective potential of the protonated water–dimer has a single-well only.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy